Psychometric Properties and Cut-Off Points of Persian Version of PPRI 12-Items among Older Veterans in Iran - Leila Ghahremani; Fatemeh Maghsoudi; Abdolrahim Asadollahi (Shiraz University of Medical Sciences, 2022)
Background: Aging and retirement are a passage to a new course of ​​life for veterans. The role of army grandparents in relation with their adult children is important; therefore, it is necessary to study grandparent-adult children interactions during retirement. Unfortunately, there was no Iranian version of an instrument to measure this interaction. Hence, the study aimed to evaluate the Persian version of the Perceived Parenting Roles Inventory (PPRI-2019). The translation process was conducted based on WHO's guidance of instruments translation and adaptation. Methods: The research method was descriptive and had a psychometric type. A total of 251 grandparents were randomly selected from the Iranian Veterans Association. The PPRI and demographic questionnaire were used to gather data at the end of 2019. The scale structure was evaluated using confirmatory factor analysis (CFA). Cronbach's alpha assessed internal consistency and the optimal cut-off points were obtained by calculating the area under the curve (ROC). Data were analyzed using IBM-SPSS version 26 and AMOS version 24. Results: The construct validity of PPRI based on CFA showed that the two subscales explained a total of 73.017 % of the variance. The PPRI scale demonstrated excellent reliability, and Cronbach's alpha obtained 0.792 for the entire scale (p< 0.000). The optimal cut-off point of PPRI was 19.50, with a sensitivity of 100%, a 1-specificity of 0.127. Conclusions: Based on the results, the Persian version of PPRI is a valid and reliable tool that other researchers can use to measure perceived parenting roles among other retirees. But further investigations are suggested.